DDE Transposases: Structural Similarity and Diversity - Nesmelova, Irina V. (2010)
DNA transposons are mobile DNA elements that can move from one DNA molecule to another and thereby deliver genetic information into human chromosomes in order to confer a new function or replace a defective gene. This process requires a transposase enzyme. During transposition DD[E/D]-transposases undergo a series of conformational changes. We summarize the structural features of DD[E/D]-transposases for which three-dimensional structures are available and that relate to transposases, which are being developed for use in mammalian cells. Similar to other members of the polynucleotidyl transferase family, the catalytic domains of DD[E/D]-transposases share a common feature: an RNase H-like fold that draws three catalytically active residues, the DDE motif, into close proximity. Beyond this fold, the structures of catalytic domains vary considerably, and the DD[E/D]-transposases display marked structural diversity within their DNA-binding domains. Yet despite such structural variability, essentially the same end result is achieved.